Chronic diarrhoea in adults: what not to miss. Issue 3 (May 2019) - Major, Giles A.D.; Gunn, David
Abstract : Purpose of review: Chronic diarrhoea remains a diagnostic challenge, with numerous causes and few effective symptomatic treatments. This review focuses on new methods for diagnosis of common disorders and alerts readers to rarer causes through a systematic approach to the underlying mechanisms. Recent findings: New strategies are emerging to stratify the need for endoscopic investigation. Faecal immunochemical testing, combined with standard blood tests, shows promise in excluding colorectal cancers, adenoma and inflammatory bowel disease, challenging the current use of faecal calprotectin. Serum analysis for markers of bile acid synthesis has been refined, potentially streamlining diagnostic pathways of bile acid malabsorption for those who are unable to access nuclear medicine scans, but the positive predictive value of faecal elastase in low prevalence populations has been questioned. Novel markers such as volatile organic compounds and stool DNA analyses continue to develop. Summary: A systematic approach to investigation of chronic diarrhoea will ensure all relevant causes are considered and minimize the chance of a missed diagnosis. Combination of clinical features with noninvasive testing supports a judicious approach to endoscopic investigations but further innovation will be needed to resolve the diagnostic challenge that diarrhoea poses.